Countrywide Survey of Plants Used for Liver Disease Management by Traditional Healers in Burkina Faso - Tibiri, André; Boria, Sébastien; Traoré, Tata Kadiatou; Ouédraogo, Noufou; Nikièma, Aude; Ganaba, Souleymane; Compaoré, Jean-Marie; Ouédraogo, Issiaka; Guissou, Innocent Pierre; Carraz, Maëlle (Frontiers in Pharmacology, 2020)
Liver disease is highly prevalent in Africa specially in the western African country Burkina Faso, due to the presence of multiple biological and chemical aggressors of the liver. Furthermore, diagnosis and appropriate care for liver disease is uneven and usually insufficient. This drives local communities to turn to folk medicine based on medicinal plants from healers. Small scale, ethnopharmacological studies on reputed hepatoprotective plants have been carried out in defined regions worldwide but so far, no study has been carried out on a countrywide scale. Therefore, we have explored traditional healers’ practices in all thirteen regions of Burkina Faso. We interviewed 575 healers and we compiled a database with 2,006 plant entries. Here we report results on liver nosology, liver pathologies, medicinal plants used for liver disease and traditional practices, through the lens of Burkinabe healers. Our goal was to give a full inventory of medicinal plants used to treat liver disease and to determine if there was consensus on the use of specific plants for specific symptoms. Analysis of the medicinal plants in use across the whole country provides local communities with a wider evidence base to determine which plants may be more effective in treating liver disease and could provide the scientific community, with a shortlist of plants suitable for chemical and pharmacological investigation to validate the plants therapeutic role.